Women in mathematics : the addition of difference - Henrion, Claudia, 1958- (Race, gender, and science., 1997)
"Mathematics is often described as the purest of the sciences, the least tainted by subjectivity or cultural influences. Theoretically, the only requirement for a life of mathematics is mathematical ability. And yet we see very few women mathematicians. The myth that women are no good at math is deeply entrenched in our culture, perpetuated by headlines in newspapers ("Do Boys Have a Math Gene?") and a focus on "math anxiety." Many people are therefore surprised to learn that in the United States, 46 percent of the bachelor's degrees in mathematics go to women. Why then does they myth continue? Many factors contribute, but an important one is the lack of visible women mathematicians. Their presence diminishes dramatically as one goes through the "mathematics pipline": women earn only about 24 percent of the math Ph. D.s and make up less than 6 percent of the full-time mathematics faculty at doctorate-granting institutions in the U.S. (They represent less than 3 percent of the tenured mathematics professors at these institutions.) Based upon a series of nine intensive interviews with prominent women mathematicians throughout the United States, this book investigates the role of gender in the complex relationship between the mathematician, the mathematical community, and mathematics itself."--Back cover